2020
DOI: 10.3390/polym12102394
|View full text |Cite
|
Sign up to set email alerts
|

Axial Orientation of Co-Crystalline Phases of Poly(2,6-Dimethyl-1,4-Phenylene)Oxide Films

Abstract: Films exhibiting co-crystalline (CC) phases between a polymer host and low-molecular-mass guest molecules are relevant for many applications. As is usual for semi-crystalline polymers, axially oriented films can give relevant information on the crystalline structure, both by Wide Angle X-ray diffraction fiber patterns and by polarized Fourier-transform infrared spectroscopy. Axially oriented CC phases of poly(2,6-dimethyl-1,4-phenylene)oxide (PPO) with 1,3,5-trimethylbenzene (mesitylene) can be simply obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The polarized FTIR spectra of the axially oriented α PPO films before and after 8 wt% of BA uptake are shown in Figure 6 . In agreement with the literature [ 30 ], the FTIR peaks (at 773, 756, 495 and 414 cm −1 ) typical of the α NC host phase were dichroic (e.g., S p,495 = +0.33).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The polarized FTIR spectra of the axially oriented α PPO films before and after 8 wt% of BA uptake are shown in Figure 6 . In agreement with the literature [ 30 ], the FTIR peaks (at 773, 756, 495 and 414 cm −1 ) typical of the α NC host phase were dichroic (e.g., S p,495 = +0.33).…”
Section: Resultssupporting
confidence: 91%
“…In this paper, we characterized films of sPS and PPO including BA molecules in their amorphous and crystalline phases. In particular, axially oriented sPS and PPO films [ 30 ] were used to obtain information on the crystalline structure by WAXD fiber patterns, as well as information on the aggregation and orientation of the guest molecules in the polymeric amorphous and crystalline phases, by polarized FTIR measurements. The present study shows that the NC δ form of sPS not only avoids additive aggregation but also leads to the separation of BA dimers and, hence, the appearance of vibrational peaks typical of vapor phase molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 collects in its last column the crystalline forms (α or β) of all films characterized in this study together with those already reported in the literature ( Khulbe et al, 2000 ; Daniel et al, 2011 ; Nagendra et al, 2019 ; Golla et al, 2020b ; Nagendra et al, 2021a ; Nagendra et al, 2021b ). In Table 1 , the guest molecules are ordered on the basis of their solubility parameter (second column) while the used crystallization methods are indicated in the fourth column.…”
Section: Resultsmentioning
confidence: 98%
“…Axially amorphous oriented films were obtained by stretching PPO amorphous films in the temperature range 220-230 • C up to draw ratio 4-5. Films exhibiting axial orientation of α NC phase were obtained by axial stretching of PPO/mesitylene CC films at 170-175 • C up to draw ratio 4 and by subsequent mesitylene removing through sorption/desorption procedures of acetonitrile at room temperature for 2 h [71]. PPO/mesitylene CC films, with thickness of nearly 150 µm, were obtained by casting from 3.5 wt% mesitylene solution at room temperature.…”
Section: Methodsmentioning
confidence: 99%